Risk assessment of zinc oxide, a cosmetic ingredient used as a UV filter of sunscreens. (3rd April 2017) - Kim, Kyu-Bong; Kim, Young Woo; Lim, Seong Kwang; Roh, Tae Hyun; Bang, Du Yeon; Choi, Seul Min; Lim, Duck Soo; Kim, Yeon Joo; Baek, Seol-Hwa; Kim, Min-Kook; Seo, Hyo-Seon; Kim, Min-Hwa; et al.
ABSTRACT: Zinc oxide (ZnO), an inorganic compound that appears as a white powder, is used frequently as an ingredient in sunscreens. The aim of this review was to examine the toxicology and risk assessment of ZnO based upon available published data. Recent studies on acute, sub-acute, and chronic toxicities of ZnO indicated that this compound is virtually non-toxic in animal models. However, it was reported that ZnO nanoparticles (NP) (particle size, 40 nm) induced significant changes in anemia-related hematologic parameters and mild to moderate pancreatitis in male and female Sprague-Dawley rats at 536.8 mg/kg/day in a 13-week oral toxicity study. ZnO displayed no carcinogenic potential, and skin penetration is low. No-observed-adverse-effect level (NOAEL) ZnO was determined to be 268.4 mg/kg/day in a 13-week oral toxicity study, and a maximum systemic exposure dose (SED) of ZnO was estimated to be 0.6 mg/kg/day based on topical application of sunscreen containing ZnO. Subsequently, the lowest margin of safety (MOS) was estimated to be 448.2, which indicates that the use of ZnO in sunscreen is safe. A risk assessment was undertaken considering other routes of exposure (inhalation or oral) and major product types (cream, lotion, spray, and propellant). Human data revealed that MOS values (7.37 for skin exposure from cream and lotion type; 8.64 for skin exposure of spray type; 12.87 for inhalation exposure of propellant type; 3.32 for oral exposure of sunscreen) are all within the safe range (MOS > 1). Risk assessment of ZnO indicates that this compound may be used safely in cosmetic products within the current regulatory limits of 25% in Korea.